Ionizable groups and conductances of the rod photoreceptor membrane - Pinto, LH (The Rockefeller University Press, 1978)
The ionizable groups and conductances of the rod plasma membrane were studied by measuring membrane potential and input impedance with micropipettes that were placed in the rod outer segments. Reduction of the pH from 8.0 to 6.8 or from 7.8 to 7.3 resulted in membrane depolarization in the dark from 8.0 to 6.8 or from 7.8 to 7.3 resulted in membrane depolarization in the dark (by 2- 3 mV) and an increased size of the light response (also by 2-3 mV). The dark depolarization was accompanied by and increased resting input impedance (by 11-35 Mω). When the pH was decreased in a perfusate in which Cl(-) was replaced by isethionate, the membrane depolarized. When the pH was decreased in a perfusate in which Na(+) was replaced by choline, an increase of input impedance was observed (11-50 Mω) even though a depolarization did not occur. These results are consistent with the interpretation that the effects of decreased extracellular pH result mainly from a decrease in rod membrane K(+) conductance that is presumably cause by protonation of ionizable groups having a pK(a) between 7.3 and 7.8. Furthermore, from these results and results obtained by using CO(2) and NH(3) to affect specifically the internal pH of the cell, it seems unlikely that altered cytoplasmic [H(+)] is a cytoplasmic messenger for excitation of the rod. When the rods were exposed to perfusate in which Na(+) was replaced by choline, the resting (dark) input impedance increased (by 26 Mω +/- 5 Mω SE), and the light-induced changes in input impedance became undetectable. Replacement of Cl(-) by isethionate had no detectable effect on either the resting input impedance or the light-induced changes in input impedance. These results confirm previous findings that the primary effect of light is to decrease the membrane conductance to Na(+) and show that, if any other changes in conductance occur, they depend upon the change in Na(+) conductance. The results are consistent with the following relative resting conductances of the rod membrane: G(Na(+)) similar to G(K(+)) more than 2-5 G(Cl(-)).